The optimal conditions for the osmotic dehydration of Syrian apricot fruits - Kalook, Wahbi Mohamad; Faleh, Adib; Sakur, Amir Al-Haj; Abdelwahed, Wassim (Journal of agricultural, environmental and veterinary sciences, 2022)
The aim of this research is to study the chemical composition of fresh apricot fruits, and to determine the optimal conditions for osmotic treatment as a primary treatment before subsequent processing operations, in the main indicators which are water loss and solid gain, using sucrose solution, and at different concentrations (40-50-60%) four different temperatures (30-40-50-60 C), for six hours period, and determining fruit per solution ratio, The results indicated that drying by osmotic pressure is one of the modern and highly effective methods in preserving biologically active substances. In addition, raising the temperature to 60°C led to a decrease in the mass transfer rate WL/SG and thus a decrease in the quality of the final product. At a temperature of 50°C, the viscosity of the solution with 60% concentration is very high, so that the water loss curves were very close to the water loss curves at 50% concentration, so the best temperature and concentration are at 50°C and 50%, respectively, and the results showed that the ratio of fruits to solution 10:1 is the optimal ratio, and the best duration of the osmotic drying process was 6 hours, The concentration of 60% and the temperature of 30 °C are the optimal conditions for maintaining the high nutritional value, biologically active compounds and antioxidant activity, by forming a layer of sucrose that protects the fruits from deterioration during subsequent manufacturing processes. The osmotic treatment reduced the effect of temperature on chemical composition and biologically active compounds, and it was possible to obtain a product with superior organoleptic properties. The osmotic treatment of apricot fruits increased the stability of the final product during the storage stages.
Keywords: apricot fruits; osmotic treatment; bioactive compounds